The Effect of Green Leadership and Green Motivation on Employee Performance - Gusna Aryunita; Muhammad Kasran; Suparni Sampetan (Golden Ratio of Mapping Idea and Literature Format, 2026)
This study aims to analyze the influence of green leadership and green motivation on employee performance at PT. Palopo Branch Pawn Shop. This study used a quantitative approach with multiple linear regression methods. This population in this study included all employees of PT. Palopo Branch Pawn Shop. The sample consisted of 48 respondents selected through a saturated sampling technique. Data were collected using a questionnaire and analyzed using validity and reliability tests, classical assumption tests, and hypothesis testing. The results indicate that green leadership and green motivation have a significant effect on employee performance, both partially and simultaneously. The findings of this study indicate that the implementation of environmentally sound leadership and work motivation based on environmental concerns can improve employee performance. This research contributes to the development of human resource management science, especially in the context of green management.